COLLECTION DEVELOPMENT STRATEGIES FOR LIBRARIES SERVING VISUALLY IMPAIRED PRIMARY SCHOOL PUPILS IN A RECESSED ECONOMY (NAU Journal of Library and Information Science, 2019)
This study was carried out to determine viable strategy for collection development in libraries serving visually impaired primary school pupils in South East Nigeria. It adopted a descriptive survey research design. The population of the study comprised four librarians in charge of the libraries in four special education centres/ schools in South East Nigeria. Interview schedule, titled “Interview Guide forLibrarians” was used to collect data from the librarians. Data collected was analyzed qualitatively. The result reveal that various strategies were used for collection development in libraries for the visually impaired primary school pupils in the zone. Most viable strategies for collection development in these libraries were through gift, donation, assistance from non-governmental organizations (NGOs), international bodies, religious groups and philanthropists. Based on the findings, it was recommended that apart from presenting their request to the government, the librarians should solicit help from NGOs, international bodies, religious groups and philanthropists to ensure steady development of their collection despite the present economic recession in the country.